Relationship between pain, fatigue, and physical activity levels during a technology-based physical activity intervention - Canori, Alexandra (J Spinal Cord Med, 2020)
Objective: The majority of individuals with spinal cord injury (SCI) experience chronic pain. Chronic pain can be difficult to manage because of variability in the underlying pain mechanisms. More insight regarding the relationship between pain and physical activity (PA) is necessary to understand pain responses during PA. The objective of this study is to explore possible relationships between PA levels and secondary conditions including pain and fatigue. Design: Prospective cohort analysis of a pilot study. Setting: Community. Participants: Twenty individuals with SCI took part in the study, and sixteen completed the study. Interventions: Mobile-health (mHealth) based PA intervention for two-months during the three-month study. Outcome measures: Chronic Pain Grade Scale (CPGS) questionnaire, The Wheelchair User’s Shoulder Pain Index (WUSPI), Fatigue Severity Scale (FSS), and PA levels measured by the mHealth system. Results: A positive linear relationship was found between light-intensity PA and task-specific pain. However, the relationship between moderate-intensity PA and pain interference was best represented by a curvilinear relationship (polynomial regression of second order). Light-intensity PA showed positive, linear correlation with fatigue at baseline. Moderate-intensity PA was not associated with fatigue during any phase of the study. Conclusion: Our results indicated that PA was associated with chronic pain, and the relationship differed based on intensity and amount of PA performed. Further research is necessary to refine PA recommendations for individuals with SCI who experience chronic pain. Trial registration: ClinicalTrials.gov identifier: NCT03773692.